Sfide quotidiane delle giovani musulmane italiane in qualità di “testimoni di una terra di confine” - Ivana Acocella (Storia delle Donne)
The aim of the article is to propose a different perspective on the issue of Muslim women, focusing on the point of view of second generations, i.e. young people born and raised in a Western context. On the “boundary” between two socio-cultural worlds –the Muslim context known through the family and the Western context in which they are growing up– young Muslim women experience hybrid forms of socialisation on a daily basis, developing “fluctuating identity markers” that are both contextual and transnational in an attempt to reconstruct a unity that does not inevitably have to be limited to a single reality. This article will therefore aim to explore the subjectivation strategies that may be produced as a result of the biographical challenges associated with the peculiar condition of “witnesses of a borderland” of young Muslim women. Such challenges and strategies of subjectification can bring out both the symbolic, structural and positioning boundaries of identity, and the spaces of dissolution of the same categories of belonging/reference, thus revealing their conventionality, contextuality and historicity.